A reappraisal of leaf morphology in Aponogeton natans (Aponogetonaceae) - Manawaduge, Chapa G.; Yakandawala, Deepthi; Les, Donald H. (Phytotaxa, 2016)
The aquatic monocotyledon genus Aponogeton L.f. (Aponogetonaceae) consists of about 57 species distributed mainly in the tropical or subtropical regions of the Old world. Aponogeton natans (L.) Engler & Krause is the type species of the genus and occurs in India, Pakistan and Sri Lanka. During recent field work, which focused exclusively on Sri Lankan Aponogeton, we were unable to satisfactorily reconcile our collections of A. natans with the morphological descriptions given in several previously published accounts globally, as all description indicated the presence of submersed leaves. Detail investigation carried out with literature and the type specimens revealed that the presences of submersed leaves is only a misconception that was propagated by a misinterpretation of the Latin description provided by Krause & Engler in 1906. To clarify the nature of the foliage in A. natans we provide here a revised morphological description of this taxon along with an illustration and images.